2019
DOI: 10.29333/pr/5731
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Emotional Violence: Relationship between University Students according to their Demographic Characteristics

Abstract: The aim of this study is to determine the level of exposure to emotional violence of university students. In addition, it was also tried to identify the relationship between the emotional violence exposure level and the variables of university students' age, gender, whether they get psychological support before and after the university or not, and the school they attend. This research is a survey model research using quantitative data. The participants of this study are 701 (415 females and 286 males) universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…It is seen that the perceptions of being insulted, ignoring, suppression, offending, humiliation and shouting about the categories obtained from women's views on emotional violence overlap with behaviors involving emotional violence in the literature (Doyle 2020;Domenech Del Rio & Sirvent Garcia Del Valle, 2017;Eskici & Saatçioğlu Tınkır, 2019;Follingstad and Edmundson, 2010;Pérez-Marco et al, 2020;Tenkorang et al, 2017). In a study on experiences of intimate partner violence, women reported that they were exposed to humiliation, humiliation, restriction of communication with family and friends, threats of physical harm, being banned from leaving the house, or being locked up in the house (Doyle, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is seen that the perceptions of being insulted, ignoring, suppression, offending, humiliation and shouting about the categories obtained from women's views on emotional violence overlap with behaviors involving emotional violence in the literature (Doyle 2020;Domenech Del Rio & Sirvent Garcia Del Valle, 2017;Eskici & Saatçioğlu Tınkır, 2019;Follingstad and Edmundson, 2010;Pérez-Marco et al, 2020;Tenkorang et al, 2017). In a study on experiences of intimate partner violence, women reported that they were exposed to humiliation, humiliation, restriction of communication with family and friends, threats of physical harm, being banned from leaving the house, or being locked up in the house (Doyle, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…When the literature is examined, it is seen that there are studies (Eskici & Saatçioğlu Tınkır, 2019;Gilbar et al, 2020;Jezl et al, 1996;Khosravi et al, 2011;Lohman et al, 2013;Molina, 2020;Semahegn & Mengistie, 2015) supporting the categories (feelings of inadequacy, desire to dominate, inability to communicate properly, anger control problems, history of domestic violence, physical health problems and socio-cultural differences) obtained from the answers given by women regarding the reasons for emotional violence by their partners in intimate relationships. In a study on early maladaptive schemas and intimate partner violence with women, it was revealed that verbal and psychological abuse in married life was associated with schema domains of guilt and shame, emotional deprivation and insecurity (Khosravi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although each student has a learning style (VAK), most students tend to have one of the dominant learning styles (Muwardi, 2013). In university life, students share a lot with their friends not only in school but also in their private life with students from different cultures of different regions is one of the biggest difficulties of university life in the first stage (Eskici and Saatçioğlu Tinkir, 2019).…”
Section: The Concept Of Learning Stylementioning
confidence: 99%
“…Young adults even use social media to find solutions when they encounter problems and crises (Uzakgiden, 2019). This over‐reliance on social media may affect young adults' problem‐solving skills as well as their efforts to belong to a group and be accepted in social network sites (Eskici & Tinkir, 2019). Moreover, being busy with social media may make them vulnerable to violence, especially emotional violence.…”
Section: Introductionmentioning
confidence: 99%